Pengaruh Faktor Pendidikan Terhadap Akses Dan Kepatuhan Pengobatan Malaria Di Kabupaten Sikka Tahun 2018 - Arnoldina Dolfina Dua Weni (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: to determine the effect of educational factors on the access and compliance of malaria treatment in Sikka District which is currently leading to the stage of malaria elimination.Methods: The design of this study was a cross sectional observational analytic study conducted in seven malaria-endemic health centers in Sikka based on 2016 cases in April-May 2018. Information on medication practices and the use of anti-malarial drugs was collected using interview techniques using a structured questionnaire. A total of 32 samples were obtained from malaria patients 15 years years old who had previously undergone malaria treatment. Confirm the results of blood tests using a microscope. Results: Fisher Exsact statistical test results using SPSS education and access variables obtained p value 0,012 <0,05 indicates that there is an influence between the level of education to access of treatment and p value of 0,227> 0,05 for education variables and adherence to treatment shows no influence level of education with adherence of malaria treatment. Conclusion: There is an influence of educational factors on the appropriateof access to malaria treatment, but has no effect on adherence of malaria treatment in Sikka District.